Testing the repatriated for SARS-Cov2: Should laboratory-based quarantine replace traditional quarantine?. Issue 34 (March 2020) - Lagier, Jean Christophe; Colson, Philippe; Tissot Dupont, Hervé; Salomon, Jérôme; Doudier, Barbara; Aubry, Camille; Gouriet, Frédérique; Baron, Sophie; Dudouet, Pierre; Flores, Rémi; Ailhaud, Lucie; Gautret, Philippe; et al.
Abstract: Background: An ongoing epidemic of respiratory diseases caused by a novel coronavirus (COVID 2019, SARS-CoV2) started in Wuhan, Hubei, in China at the end of December 2019. The French government decided to repatriate the 337 French nationals living in Wuhan and place them in quarantine in their home country. We decided to test them all for SARS-Cov2 twice in order to reduce anxiety among the population and decision-makers. Methods: We investigated the presence of SARS-CoV-19 in asymptomatic carriers by testing all repatriated patients within the first 24 h of their arrival in France and at day 5. Viral RNA was extracted from pooled nasal and oropharyngeal swab fluids or sputum in the absence of nasal/oropharyngeal swabs. Detection of SARS-CoV-2 RNA was then carried out using several real-time reverse transcription (RT)-PCR assays. Results: We tested 337 passengers at day 0 and day 5. All the tests for SARS-CoV2 were negative. By optimising the sampling process, sending samples sequentially and reducing the time-scale for biological analysis, we were able to test the samples within 5 h (including sampling, shipment and biological tests). Conclusion: Optimising our procedures reduces anxiety and reassures the population and decision makers.